The role of the public sector in incentivizing the uptake of climate-resilient seeds in Uganda - Kuteesa, Annette; Katunze, Miriam (Economic Policy Research Centre, 2016)
Access to quality seeds is important in building climate resilient value chains because it promotes improved quantity and quality of agricultural products. The need to invest in climate resilient seed has become critical in Uganda given the increasing demand for food both for consumption and trade, declining per capita food production and land under agriculture, and increased frequency and intensity of climate hazards. Threats posed by climate change call for a focus on more resilient strategies and technologies that can yield more efficient use of the available resources. Incentives directed at supporting climate risk management (CRM) must thus consider the diverse and dynamic nature of roles and needs of the value chain actors by addressing the challenges in the seed sector, mainstreaming climate changes in all relevant policies, exploring and putting in place financial incentives to encourage product development that supports CRM, supporting access to the dissemination and communication of climate information and integrating of the value chain approach.